PENGENDALIAN JAMUR PENYEBAB BUSUK BENIH TUSAM (Pinus merkusii Jungh et de Vriese) DENGAN ASAP CAIR KAYU LABAN (Vitex pubescens Vahl) - Alviolita, Zefanya; Oramahi, Hasan Ashari; Diba, Farah (Universitas Tanjungpura, 2014)
This study aims to determine the effectiveness of liquid smoke from Laban wood for controlling fungi that cause damping off on pine seeds and to determine the optimal concentration and temperature of pyrolysis of liquid smoke from Laban wood. The experiment was conducted at the Laboratory of Wood Technology, Faculty of Forestry, University of Tanjungpura Pontianak. Mucor sp is the species of fungi which used to in vitro test to determine the inhibition value. Research using RAL Factorial methods with two treatment factors, first treatment factor is the concentration of liquid smoke from Laban wood with 5 levels i.e. 0%, 2.5%, 5%, 7.5%, and 10%. The second treatment factor is the temperature of the pyrolysis liquid smoke of Laban wood with 3 levels i.e. 350ºC, 400ºC and 450ºC. Five replicates are conducted for all treatments. Tests carried out using a PDA medium mixed with liquid smoke from Laban wood with each concentration. Results of research showed that the concentration of liquid smoke from Laban wood is very significant effect on the inhibition of the growth of the fungus Mucor sp. Meanwhile the pyrolysis temperature and the interaction of liquid smoke from Laban wood had no significant effect. Liquid smoke from Laban wood at a concentration of 10% with a pyrolysis temperature of 400°C is the best treatment because it can inhibited the growth of fungal Mucor sp. with the highest value (96.33%). This antifungal activity rate fulfills the very strong category inhibition. Liquid smoke from Laban wood can be used as biopesticide to overcome damping off fungi on Pine seed. Keywords : Laban wood, Mucor sp., liquid smoke, damping off, Pinus merkusii